The Archaeology of Afghanistan. - Stockwell, Peter.
1 online resource (752 pages)
Keywords: First published in 1978, this was the first book in English to provide a complete survey of the immensely rich archaeological remains of Afghanistan. It has now been thoroughly revised and brought up to date to incorporate the latest discoveries and research.